Sinonasal and Laryngeal Carcinoma in Children: Correlation of Imaging Characteristics with Clinicopathologic and Cytogenetic Features - Robson, C.D. (AJNR Am J Neuroradiol, 2010)
BACKGROUND AND PURPOSE: Pediatric upper airway carcinoma is uncommon, symptoms are nonspecific, and diagnosis is often delayed. In this study, we describe the imaging, cytogenetics, and clinical courses of 4 patients with pediatric upper airway carcinoma. MATERIALS AND METHODS: Four patients with upper airway carcinoma were identified during a 2.5-year period. CT (n = 4) and MR imaging (n = 3) studies, tumor histopathologic features and cytogenetics, patient treatment, and clinical course were reviewed. RESULTS: Patients were aged 12 to 15 years. One tumor involved the larynx with poorly defined margins and heterogeneous enhancement; 1 heterogeneously enhancing tumor involved the epiglottis with necrotic cervical lymphadenopathy. There were 2 enhancing sinonasal tumors with bony destruction in 1 tumor. Tumors had a relatively short relaxation time on FSEIR MR imaging. Histopathologic examination revealed poorly differentiated squamous cell carcinoma (n = 3) and well-differentiated squamous cell carcinoma (n = 1). Cytogenetic analysis revealed chromosomal abnormalities in 3 tumors: 2 showed a chromosomal translocation t(15;19), and 1 showed a chromosomal translocation t(1;5) and loss of a portion of chromosome 22q. Results of in situ hybridization for EBV were negative (n = 3). Treatment included tumor resection (n = 2), chemotherapy (n = 4), and radiation therapy (n = 3). Patients with t(15;19) died months after diagnosis. Two patients were alive at 8-year follow-up. CONCLUSIONS: Childhood carcinoma of the upper airway is uncommon but should be considered in the diagnosis of upper airway tumors that display aggressive imaging characteristics. Carcinoma with t(15;19) is rare but has been reported, usually in young patients with midline carcinoma of the neck or mediastinum, with a rapidly fatal course.